Progress and control in development of single layer graphene membranes. (May 2020) - Tincu, B.; Avram, M.; Avram, A.; Tutunaru, O.; Tucureanu, V.; Matei, A.; Burinaru, T.; Comanescu, F.; Demetrescu, I.
Abstract: Recent approaches in graphene transfer on different substrates and nanostructured surfaces have opened up new potential applications such as: pressure sensors, separation membranes, electrochemical sensors. Graphene single layer is a promising membrane material, due to chemically inert, large specific surface area with hydrophobic property. In this work, single layer graphene have been synthesized by CVD on copper catalyst and transferred by three different wet chemical transfer methods on Si/SiO2 holes of approximatively 7 μm diameter. The novelty of this study is the introduction of a vacuum step to help remove liquids from underneath the graphene layer while maintaining the structural integrity of the membrane. Raman spectroscopy was performed to analyze the number of layers and the quality of graphene. The morphology of the graphene transferred on the holes were examined using scanning electron microscopy (SEM). Graphical abstract: Image 1 Highlights: Single Layer Graphene was prepared by CVD method on the copper foils as metal catalyst. Single Layer Graphene was successfully transferred on Si/SiO2 holes. Samples of graphene based membranes were comparatively characterized by optical, Raman Spectroscopy and Scanning Electron Microscopy.